Pedophilia and Possibilities of Social Reactions - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
Sexual abuse of children is a widespread problem with serious clinical, social, moral and juridical implications. The experts keep warning that about 15 per cent of children are being sexually abused in many possible ways. načina (American Academy of Child and Adolescent Psychiatry, 2004; Levine, 2002). Statistics on the incidence of this type of crime are extremely alarming, and, above all, they probably represent only the tip of an iceberg. A need for well conducted researches of those persons whose sexual aggression is directed toward children, as well as shedding light on specific problems which have to do with incestuous offenders and which would be the basis for designing preventive programs and for eventual prediction and control, is extremely obvious in the context of this type of sexual violence. We declare this, being, before all, aware of the fact that the subject of our eventual attention and protection in this situation is far more vulnerable, sensitive and helpless than any adult victim of sexual offences, and, therefore, the consequences of this act are far more complicated and more difficult to be corrected, if they can be corrected at all.